Investigation of the Risk of Social Media Addiction and Individual-Social Problems in Adolescents - Duman, Damla; Turan, Nazan (My University, 2024)
Objective: This study aimed to investigate the relationship between social media addiction and individual as well as social problems in adolescents. Method: A cross-sectional, relational design was employed from October 2020 to October 2021, involving 1007 students. Data were collected using the Participant Information Form (PIF), Social Media Addiction Scale for Adolescents (SMASA), and Multidimensional Adolescent Rating Scale (MARS). Results: The findings revealed no direct relationship between social media addiction risk and individual or social problems in adolescents. However, social media addiction scores significantly varied based on the duration and frequency of social media use. Additionally, the study identified associations between the duration of social media use and factors such as depression, school and family problems, confusion, and intrusive thoughts among adolescents. Conclusion: The results indicate that both the duration and frequency of social media use influence adolescents' social media addiction levels and their psychological well-being.
Keywords: Adolescence; social media addiction; adolescence problems